Purchase Intention of Z-Generation Consumers towards Traditional Cultural Products - Zheng, Tong; Huang, Ying; Wang, Qiyu; Wang, Siqing; He, Zhengbo (Transactions on Economics, Business and Management Research, 2024)
With the continuous evolution of society and culture, the purchasing inclination of the new generation of consumers towards traditional cultural products has undergone significant changes. Despite in-depth research by domestic scholars on variables such as traditional cultural elements and flow experience, their actual impact in the modern consumer market has not received sufficient attention. This study, aiming to explore the intrinsic connection between traditional cultural elements, flow experience, and purchase intention of Z-generation consumers, takes flow experience as a mediator and purchase intention as the dependent variable. Through in-depth analysis of questionnaire survey data using SPSS 26.0 software, this paper confirms the significant positive impact of traditional cultural elements on purchase intention and reveals the mediating role of flow experience in this process. The research results indicate that as the main force of the new generation of consumers, Z-generation consumers deeply identify with and love traditional cultural elements, preferring to purchase products incorporating these elements and experiencing the joy of flow experience during use. This provides new opportunities for the development and application of traditional cultural element products in modern society. Based on this, this paper proposes a series of strategic recommendations, including integrating traditional cultural elements into product design, enhancing consumer participation, and blending traditional culture with modern consumption trends through innovative means to meet the needs of Z-generation consumers.